A phase 1 safety study of veliparib combined with cisplatin and etoposide in extensive stage small cell lung cancer: A trial of the ECOG–ACRIN Cancer Research Group (E2511). Issue 1 (July 2015) - Owonikoko, Taofeek K.; Dahlberg, Suzanne E.; Khan, Saad A.; Gerber, David E.; Dowell, Jonathan; Moss, Rebecca A.; Belani, Chandra P.; Hann, Christine L.; Aggarwal, Charu; Ramalingam, Suresh S.
Highlights PARP inhibitor potentiated DNA damaging agents in preclinical models of SCLC. The combination of veliparib, cisplatin, and etoposide was safe in untreated SCLC. The recommended phase II dose (RP2D) of this combination regimen is now established. Veliparib (100 mg bid), cisplatin (75 mg/m2), and etoposide (100 mg/m2) is the RP2D.